Effects of Feeding Distillers Dried Grains with Solubles (DDGS) on Feed Intake and Milk Production Performance of Crossbred Cows - Madhavatar, Mahesh P; Shah, Shailesh V; Wadhwani, Kishan N; Lunagariya, Pravin M; Modi, Rakesh J; Patel, Ashish C (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Present experiment was conducted to study the performance of feeding Distillers Dried Grains with Solubles (DDGS) on milk production  on 18 HF × Kankrej (75:25) advance pregnant crossbred heifers, which were distributed into three treatment groups (T1, T2 and T3)  comprising of 6 animals each. The total duration of experiment was 300 days. Animals were offered three different types of total mixed  rations containing 20, 10 and 0% Soy DOC, and 0, 10 and 20% rice DDGS (RDDGS) in T1, T2 and T3 groups, respectively. The overall mean  values of DMI (kg/animal/day, and kg/100 kg body weight) in crossbred cows were 11.81±0.12 and 2.66±0.05, respectively. Average DMIs  in T1, T2 and T3 groups of crossbred cows were 11.99±0.23, 11.81±0.22 & 11.62±0.19 kg/animal/day (p>0.05), and 2.82±0.10, 2.60±0.09  & 2.55±0.08 kg/100 kg body weight (p
Keywords: Crossbred cows, DDGS, Feed intake, Milk production